Mewujudkan Sustainable Development Goals (SDGS) MelaluiSekolah Lapang Terhadap Perkembangan Pengetahuan Petani Kopi Di Desa Hutagurgur, HumbangHasundutan, Sumatera Utara - Ainun Najib; David Ndaru Aji Pramudya; Mirza Andrian syah (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
Coffee has become a promising leading commodity in the North Sumatra region. However, in the practice of coffee cultivation at the location, issues were found where most farming practices did not comply with Good Agriculture Practice (GAP). One way to support the achievement of SDG Goal 8: decent work and economic growth can be through community service. The Edu Farmers International Foundation, through its "Farming for the Nation" program, conducted mentoring activities for coffee farmers in the form of field schools. The aim of this activity was to assist coffee farmers in Hutagurgur Village in adhering to proper GAP practices to achieve the maximum quality and quantity of coffee. The method involved observing problems and potentials, formulating solutions, planning field schools, determining topics and schedules for the field schools, and conducting the field schools. The results showed that farmers experienced an increase in knowledge and implementation by 25-400%. However, the impact on productivity has not yet been observed, as the assessment was not conducted during the main harvest season.